New slip-line field model based on dead metal zone and material flow in negative rake orthogonal cutting - Altan, Erhan; Emiroglu, Ugur (SPRINGER HEIDELBERG, 2022)
A new slip-line field model for orthogonal cutting with negative rake angle tools was proposed in this study. The presence of a dead metal zone in front of a cutting tool with a negative rake angle and also bidirectional material flow was considered in the new model. According to this model, a partial of the removal material becomes chip, while the rest moved downward into the workpiece. Cutting forces and the amount of the depth of cut that moved downward into the workpiece were determined by using this model. Under particular cutting conditions, orthogonal cutting experiments were carried out using a shaping-based computer-controlled quick stop device. It was experimentally observed that the material exhibited bidirectional flow during cutting with tool having negative rake angle. The amount of materials in both formations: material moved toward onto the cutting tool and under it, changed depending on the cutting conditions and the variation of negative rake angle. Additionally, the position of the stagnation point which determines the material flow was defined by the model. Finally, it was seen that the experimental and analytical results were in good agreement.
Keywords: Negative rake angle; Slip-line field model; Material flow; Orthogonal cutting; SIMPLE PREDICTIVE MODEL; CHIP FORMATION; THEORETICAL-ANALYSIS; ABRASIVE PROCESSES; BASIC MECHANICS; ANGLE; REMOVAL; TOOLS; Engineering